Exome sequences and multi‐environment field trials elucidate the genetic basis of adaptation in barley. (27th June 2019) - Bustos‐Korts, Daniela; Dawson, Ian K.; Russell, Joanne; Tondelli, Alessandro; Guerra, Davide; Ferrandi, Chiara; Strozzi, Francesco; Nicolazzi, Ezequiel L.; Molnar‐Lang, Marta; Ozkan, Hakan; Megyeri, Maria; Miko, Peter; et al.
Summary: Broadening the genetic base of crops is crucial for developing varieties to respond to global agricultural challenges such as climate change. Here, we analysed a diverse panel of 371 domesticated lines of the model crop barley to explore the genetics of crop adaptation. We first collected exome sequence data and phenotypes of key life history traits from contrasting multi‐environment common garden trials. Then we applied refined statistical methods, including some based on exomic haplotype states, for genotype‐by‐environment (G×E) modelling. Sub‐populations defined from exomic profiles were coincident with barley's biology, geography and history, and explained a high proportion of trial phenotypic variance. Clear G×E interactions indicated adaptation profiles that varied for landraces and cultivars. Exploration of circadian clock‐related genes, associated with the environmentally adaptive days to heading trait (crucial for the crop's spread from the Fertile Crescent), illustrated complexities in G×E effect directions, and the importance of latitudinally based genic context in the expression of large‐effect alleles. Our analysis supports a gene‐level scientific understanding of crop adaption and leads to practical opportunities for crop improvement, allowing the prioritisation of genomic regions and particular sets of lines for breeding efforts seeking to cope with climate change and other stresses. Significance Statement: We analysed exome sequence data and life history traits measured in multi‐environment trials of a diverse panel of 371 domesticated barley lines to explore the genetics of crop adaptation. G×E interactions indicated adaptation profiles that varied for sub‐populations defined from exomic data. Exploration of circadian clock‐related genes associated with days to heading revealed complexities in G×E effect directions, and the importance of latitudinally based genic context in the expression of large effect alleles. Analysis provides practical information for future crop breeding.